Encountering the parables in contexts old and new - Goud, Thomas E.; Cousland, J. R. C.; Harrison, John (Library of New Testament studies, 2023)
"This volume examines the material elements and mundane aspects of daily life in the first century that underlie Jesus' Synoptic parables"--